VIDEO WEB DRAMA SERIES FOR COMBATING DISINFORMATION: AN INNOVATION IN REACHING AND TEACHING AUDIENCE - Santi Indra Astuti; Lumakto Giri; Nuril Hidayah (ASPIKOM Jabodetabek Region, 2020)
Fighting disinformation through anti-hoax training has been successfully carried out all over Indonesia, following the massive anti-hoax campaign. However, the methods of training and teaching fact checking as the basics of the anti-hoax movement to reduce hoaxes and its harmful effects among the public need to be revised. In finding the solution, a new and innovative approach was launched. A web drama series in the form of videos depicting story in popular style was produced and screened in 56 workshops and uploaded in YouTube channel. Analyzing survey based pre-test and post-test questionnaires, toward 603 housewives and 809 young people who represented targets of the Stop Hoax Indonesia (SHI) project in 2019 resulted in some conclusions. For housewives, the web video drama series has added knowledge and motivates them to do fact checking. But for young people, though they show motivations to do fact checking, they weren’t able to discern material regarding the role of journalism as the important element of verifying information. These findings marked the importance of revising training materials using the web video drama to reach maximum effects on various targets. On the other hand, research results have reinforced the need to innovate teaching materials in order to enhance participants' experience in dealing with hoax or disinformation in real life. More videos packed with popular culture style are recommended.